MORPHOFUNCTIONAL CHANGES IN THE HISTOLOGICAL STRUCTURES OF THE THYMUS OF WHITE RATS DUE TO ZIN DEFICIENCY - Turdiyev M.R. (GLOBAL SCIENTIFIC RESEARCH AND INTELLECTUAL PURSUITS, 2025)
Abstract: In this study, a comparative analysis of morphological and microcirculatory changes in the thymus of white rats with alimentary zinc deficiency was conducted. During the experiment, dynamic changes in the lymphoid structures of the thymus, the degree of differentiation of thymocytes, the cortico-medullary ratio, and the reaction of stromal elements were morphometrically assessed. Disorders of parenchymal-stromal balance of the thymus, morphometric indicators of lymphoid tissue, a decrease in the number of lymphoid cells, as well as an increase in the thickness of the vessel wall and a decrease in the internal diameter of the organ were revealed.